(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Instagram As Effectiveness Communication Media for Agricultural Products Marketing by Panenpa Indonesia. Instagram is one of the most widely used media in marketing, one of which is to promote products. The Covid-19 pandemic situation has triggered an increase in Instagram users, thus requiring business actors to ensure that the use of Instagram as a marketing communication medium runs effectively. The purpose of this study is to analyze the characteristics of Panenpa Indonesia’s Instagram, analyze the characteristics of Panenpa Indonesia’s Instagram access, analyze the effectiveness of Instagram as a marketing communication medium, and analyze the relationship between Instagram characteristics and the characteristics of Instagram access to Instagram effectiveness. The data analysis method in this study uses descriptive analysis and the SEM-PLS technique. The results showed that the characteristics of Instagram belong to the attractive category, because the information is complete, the grammar is good, the photos are attractive, and the color composition is attractive. Characteristics of Instagram users Panenpa Indonesia is dominated by female viewers, average diploma/graduate level of education and moderate income. The effectiveness of Panenpa Indonesia’s Instagram as a marketing communication medium is quite effective, it is explained from Instagram being able to invite moderate attention, moderate interest, moderate desire, and moderate action from Instagram users of Panenpa Indonesia. The relationship between Instagram characteristics and the characteristics of Instagram users Panenpa Indonesia has a positive relationship and has a significant effect on the effectiveness of Instagram.